Expert assessment of psychological damage in cases of violence against women. Analysis in the Ecuadorian forensic context - Francis Bone, Monica Alexandra (2022)
In Ecuador, there is dissatisfaction due to the lack of uniformity of technical and legal criteria when carrying out psychological expertise on psychological damage in cases of violence against women. This article addresses the current expert action in Ecuador regarding the assessment of psychological damage in cases of violence against women, according to the Protocol for Judicial Management and Expert Action in Cases of Violence Against Women or Family Members. This research will analyze the limitations encountered by psychology experts when assessing psychological damage, and will show the scope (benefits) that this psychological expertise represents for the legal forum (judges, prosecutors, law enforcement actors in general). Finally, as a recommendation, technical guidelines are offered to facilitate both the work of the expert and the understanding of the forensic psychological report by the judicial authorities.